Understanding learning intention complexities in lean manufacturing training for innovation on the production floor - Nai Yeen Gavin Lai; Wai Choong Foo; Chon Siong Tan; Myoung Sook Kang; Hooi Siang Kang; Kok Hoong Wong; Lih Jiun Yu; Xu Sun; Nadia Mei Lin Tan (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The Theory of Planned Behavior (TPB) is a useful framework that helps explain people's behavior across a wide range of settings. The present study adopted the TPB to investigate factors that affect the complexity of the learning intention of workers involved with a lean manufacturing training initiative. Even though workers' training has been consistently listed as a critical success factor for innovative improvement initiatives, very few studies explore direct workers' learning intentions. This is particularly true within the area of lean manufacturing training. Hence, direct workers in an automotive parts manufacturing organization were invited to participate in this study, to which 204 workers voluntarily responded. The survey data was compiled and analyzed through stepwise regression to establish the effects of the different factors on learning intention in lean manufacturing training. It was determined from the empirical results that the participants' attitude toward learning from lean manufacturing training and the perceived behavioral control factors positively affected the workers' learning intention. Organization management could look into different measures and policies to stimulate better learning effects from training programs among the participants. Actions that could foster positive attitudes and confidence of workers towards lean training initiatives will be most helpful in enabling effective and innovative lean practices on the organization's shop floors. The key theoretical and managerial implications, as well as the limitations of the study, are also discussed.
Keywords: 650; continuous improvement; lean manufacturing; learning intention; training